2019
DOI: 10.3389/fendo.2019.00203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin E-Stabilized Ultra High Molecular Weight Polyethylene on Oxidative Stress Response and Osteoimmunological Response in Human Osteoblast

Abstract: High Crosslink process was introduced in the development of joint prosthetic devices, in order to decrease the wear rate of ultrahigh molecular weight polyethylene (UHMWPE), but it also triggers the formation of free radicals and oxidative stress, which affects the physiological bone remodeling, leading to osteolysis. Vitamin E stabilization of UHMWPE was proposed to provide oxidation resistance without affecting mechanical properties and fatigue strength. The aim of this study is to evaluate the antioxidant e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Even though UHMW-PE presents lots of advantages its imperfection remains significant-it is not visible on an X-ray examination [13]. Implants made of UHMW-PE are being modified-to decrease its wear rate and the formation of free radicals that lead to oxidative stress, vitamin E is added [15]. Vitamin E is described as an antioxidant in a human's body, reacting with free radicals in cell membrane and protecting from the degradation processes (due to oxidation) and polyunsaturated fatty acids [16].…”
Section: Discussionmentioning
confidence: 99%
“…Even though UHMW-PE presents lots of advantages its imperfection remains significant-it is not visible on an X-ray examination [13]. Implants made of UHMW-PE are being modified-to decrease its wear rate and the formation of free radicals that lead to oxidative stress, vitamin E is added [15]. Vitamin E is described as an antioxidant in a human's body, reacting with free radicals in cell membrane and protecting from the degradation processes (due to oxidation) and polyunsaturated fatty acids [16].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with periodontal disease have been found to show an increased concentration of oxidation damage markers 27 . In addition, it has been reported that oxidative stress can be reduced through the use of antioxidants, including α‐tocopherol, an important lipid‐phase, free‐radical, chain‐breaking antioxidant in the body, 28 this could help explain the association between serum antioxidants (eg, vitamin E) and periodontal condition 20,29,30 . Previous studies have reported a negative association between serum and plasma levels of ascorbic acid and α‐tocopherol as an oxidative stress marker 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Massaccesi’s group reported that Vitamin E significantly increased levels of OGT, improving the ability of osteoblasts to respond to oxidative stress and ultimately reducing osteolysis caused by oxidation (Fig. 5 ) [ 115 ]. This study provides new insights into preventing osteolysis and improving the longevity of total joint replacements.…”
Section: O-glcnacylation Participates In Pathological Bone Diseasesmentioning
confidence: 99%